CSOG MFM Committee Guideline: Clinical Management Guidelines for Acute Fatty Liver of Pregnancy in China (2021) - Maternal-Fetal Medicine Committee, Chinese Society of Obstetrics and Gynecology, Chinese Medical Association; Ping Li; Yaolong Chen; Weishe Zhang; Huixia Yang; Yang Pan (Wolters Kluwer Health, 2021)
Abstract. Acute fatty liver of pregnancy (AFLP) is a rare but critical obstetric-specific disease with a high fatality rate, posing a serious threat to the safety of mothers and infants. These guidelines were specially formulated to standardize AFLP clinical pathways and to improve maternal and infant outcomes. Based on a two-round questionnaire survey, the guideline development team identified the following nine clinical issues that clinicians were most concerned about, and developed recommendations for each of them: prenatal outpatient screening for AFLP, diagnosis, preoperative risk assessment, delivery modes and timing, anesthesia methods, perinatal complications, selecting AFLP patients for artificial liver treatment, prognostic assessment, and monitoring during treatment. The guidelines cover the key issues related to AFLP diagnosis and treatment that concern clinicians.